Beyond the counter: Pharmacists’ preparedness and response strategies in terrorism-related emergencies in Quetta, Pakistan - Fahad Saleem; Fazal ur Rehman Khilji; Sajjad Haider; Qaiser Iqbal; Baharudin Ibrahim; Fatiha Hana Shabaruddin; Mohammad Bashaar (PLoS ONE, 2026)
Terrorism-related disasters (TRDs) continue to exert profound and recurring pressures on healthcare systems, particularly in vulnerable regions like Pakistan. Although pharmacists are increasingly recognized as an essential component of disaster management, there is a clear gap in the literature regarding their preparedness, experience, and specific roles in responding to TRDs particularly in low and middle-income countries. This study aimed to explore the preparedness, experiences, and response strategies of pharmacists managing TRDs at the Trauma Centre of Sandeman Provincial Hospital, Quetta, Pakistan. A qualitative design was adopted, guided by the Consolidated Criteria for Reporting Qualitative Research. Semi-structured, face-to-face interviews were conducted with pharmacists (n = 10) providing services at the Trauma Centre. Data were audio-recorded, transcribed verbatim, validated by participants, and analyzed using thematic content analysis. Analysis revealed five overarching themes: (1) pharmacists’ experiences with terrorism-related incidents and existing response mechanisms; (2) professional and personal responses to emergencies, reflecting both commitment and psychological burden; (3) preparedness challenges, including lack of disaster management training, limited awareness of policies and protocols, and inadequate understanding of triage and coordination; (4) barriers such as security risks, pharmacy curriculum deficiencies, insufficient experiential learning, and minimal involvement in planning and management activities; and (5) recommendations for strengthening capacity, including revising curricula, implementing structured training programs, conducting regular disaster drills, and expanding pharmacists’ roles in preparedness and response. Findings revealed a pronounced lack of formal training in disaster management, limited awareness of protocols and triage systems, and minimal involvement of pharmacists in planning and coordination activities. Despite strong professional commitment and frontline engagement, pharmacists’ contribution remain constrained by educational, structural, and policy-level shortcomings. The study highlights the urgent need for integrating disaster management into pharmacy curricula, implementing structured training programs and regular disaster drills, and expanding pharmacists’ roles within institutional and national disaster preparedness frameworks.